Observations and Perspectives on Adaptive Immunity to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) . (20th April 2022) - Dan, Jennifer; da Silva Antunes, Ricardo; Grifoni, Alba; Weiskopf, Daniela; Crotty, Shane; Sette, Alessandro
Abstract: Since the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic began 2 years ago, the scientific community has swiftly worked to understand the transmission, pathogenesis, and immune response of this virus to implement public health policies and ultimately project an end to the pandemic. In this perspective, we present our work identifying SARS-CoV-2 epitopes to quantify T-cell responses and review how T cells may help protect against severe disease. We examine our prior studies which demonstrate durable humoral and cell-mediated memory in natural infection and vaccination. We discuss how SARS-CoV-2–specific T cells from either natural infection or vaccination can recognize emerging variants of concern, suggesting that the currently approved vaccines may be sufficient. We also discuss how pre-existing cross-reactive T cells promote rapid development of immune memory to SARS-CoV-2. We finally posit how identifying SARS-CoV-2 epitopes can help us develop a pan-coronavirus vaccine to prepare for future pandemics. Abstract : Identification of SARS-CoV-2 epitopes permit quantification of T cells. Immunity is relatively durable after natural infection and vaccination. SARS-CoV-2–specific T cells can recognize variants of concern. Individuals with pre-existing cross-reactive SARS-CoV-2–specific T cells quickly mount robust immune responses.